2012
DOI: 10.1016/j.gaceta.2011.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Satisfacción de las mujeres con la experiencia del parto: validación de la Mackey Satisfaction Childbirth Rating Scale

Abstract: This scale is a useful instrument to measure women's satisfaction with the experience of childbirth, adapted to our context and with good psychometric properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…Other researchers have observed that women had higher satisfaction when they saw that their expectations about pain relief were met 1022 60 In the subscale ‘pain after delivery’, it was observed that women had less pain after delivery in the humanised model of maternity care than in the biomedical one, as well as less pain in the immediate postpartum period.…”
Section: Discussionmentioning
confidence: 98%
“…Other researchers have observed that women had higher satisfaction when they saw that their expectations about pain relief were met 1022 60 In the subscale ‘pain after delivery’, it was observed that women had less pain after delivery in the humanised model of maternity care than in the biomedical one, as well as less pain in the immediate postpartum period.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the Iranian version of the MCSRS can be a proper representative of functional service quality and the level of maternal satisfaction with childbirth experience at hospitals (1, 9, 12, 19, 20). In accordance with previous studies, mothers expected nurses and midwifes (as key maternity care providers) to be skilled, watchful, and compassionate towards them and their infants and to keep them away from hazards.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning women who speak Spanish, although work has been done in the field of maternal satisfaction, there are gaps in our knowledge especially with respect to women's satisfaction with preterm labor and birth. Only one validated questionnaire has been developed, the Spanish‐translated version of the P‐BESS .…”
Section: Introductionmentioning
confidence: 99%